Preparation for Grace in Puritanism: An Evaluation from the Perspective of Reformed Anthropology - Hendra Thamrindinata (Universitas Pelita Harapan, 2019)
The Puritans’ doctrine on the preparation for grace, whose substance was an effort to find and to ascertain the true marks of conversion in a Christian through several preparatory steps which began with conviction or awakening, proceeded to humiliation caused by a sense of terror of God’s condemnation, and finally arrived into regeneration, introduced in the writings of such first Puritans as William Perkins (1558-1602) and William Ames (1576-1633), has much been debated by scholars. It was accused as teaching salvation by works, a denial of faith and assurance, and a divergence from Reformed teaching of human's total depravity. This paper, on the other hand, suggesting anthropology as theological presupposition behind this Puritan’s preparatory doctrine, through a historical-theological analysis and elaboration of the post-fall anthropology of Calvin as the most influential theologian in England during Elizabethan era will argue that this doctrine was fit well within Reformed system of believe.